Tension/Compression asymmetry of a creep deformed single crystal Co-base superalloy. (March 2019) - Lenz, Malte; Eggeler, Yolita M.; Müller, Julian; Zenk, Christopher H.; Volz, Nicklas; Wollgramm, Philip; Eggeler, Gunther; Neumeier, Steffen; Göken, Mathias; Spiecker, Erdmann
Abstract: The creep behavior of a multinary single crystal Co-base superalloy has been compared for uniaxial tension and compression of 400 MPa applied along [001] at 850 °C. Creep under tensile stress proceeds two times faster than creep under compression. A detailed TEM study shows that already after ∼0.3 % creep strain planar faults are formed in both samples. While extended a/2<112> ribbons with SISF loops embedded in APBs are observed in tension, extrinsic SFs are revealed in compression. At ∼5 % creep strain SISFs confined to the γ′ phase dominate in tension, whereas extrinsic SFs and microtwins extending across both phases are the prevalent planar faults in compression. In addition, dense networks of regular a/2<101> matrix dislocations develop at the γ/γ′ interfaces in both loading scenarios. In tensile creep and early compressive creep the direct contribution of planar faults to plastic deformation is minor and does not exceed 10 % of the measured plastic strain. In contrast, thickening of microtwins appears to become an efficient deformation channel in the later stages of compressive creep. A pronounced asymmetry regarding the rafting kinetics is observed resulting in a P-type rafted and topologically inverted microstructure after ∼5 % creep in tension while hardly any rafting has occurred under compression. The pronounced rafting and related recovery processes are likely responsible for the inferior creep behavior in tension. Finally, two novel diffusion-assisted degradation mechanisms related to microtwins are shown to be active: an expansion of the γ phase into γ′ precipitates along microtwins and the formation of γ phase nuclei at planar fault intersections inside γ′. Both phenomena are hypothesized to be triggered by segregation of γ formers like Co and Cr to planar faults. Graphical abstract: Image 1